Mixed Ca/Sr salt forms of salicylic acid: tuning structure and aqueous solubility. Issue 2 (10th January 2018) - Allan, Pamela; Arlin, Jean-Baptiste; Kennedy, Alan R.; Walls, Aiden
Abstract : A series of mixed‐metal Ca/Sr and Sr/Ba salts of salicylate is presented. The a and c axes increase in length with increasing amounts of the larger cations, but the b axis contracts slightly. The aqueous solubility of the Ca/Sr series increases with increasing Sr content. Abstract : Ten isostructural single‐crystal diffraction studies of mixed cation Ca/Sr salt forms of the salicylate anion are presented, namely catena ‐poly[[diaquacalcium(II)/strontium(II)]‐bis(μ2 ‐2‐hydroxybenzoato)], [Ca1– x Sr x (C7 H5 O3 )2 (H2 O)2 ] n, where x = 0, 0.041, 0.083, 0.165, 0.306, 0.529, 0.632, 0.789, 0.835 and 1. The structure of an isostructural Sr/Ba species, namely catena ‐poly[[diaquastrontium(II)/barium(II)]‐bis(μ2 ‐2‐hydroxybenzoato)], [Sr0.729 Ba0.271 (C7 H5 O3 )2 (H2 O)2 ], is also described. The Ca/Sr structures form a series where, with increasing Sr content, the unit cell expands in both the crystallographic a and c directions (by 1.80 and 3.18%, respectively), but contracts slightly in the b direction (−0.31%). The largest percentage structural expansion lies parallel to the direction of propagation of the one‐dimensional coordination polymer that is the primary structural feature. This structural expansion is thus associated with increased M —O distances. Aqueous solubility measurements show that solubility generally increases with increasing Sr content. Thus, tuning the composition of these mixed counter‐ion salt forms leads to systematic structural changes and allows solubility to be tuned to values between those for the pure Ca and Sr species.